Malaria associated symptoms in pregnant women followed-up in Benin - Massougbodji Achille; Mévo Blaise; Borgella Sophie; Gbaguidi Gildas; Fievet Nadine; Huynh Bich-Tram; Deloron Philippe; Cot Michel (Malaria Journal, 2011)
Abstract Background It is generally agreed that in high transmission areas, pregnant women have acquired a partial immunity to malaria and when infected they present few or no symptoms. However, longitudinal cohort studies investigating the clinical presentation of malaria infection in pregnant women in stable endemic areas are lacking, and the few studies exploring this issue are unconclusive. Methods A prospective cohort of women followed monthly during pregnancy was conducted in three rural dispensaries in Benin from August 2008 to September 2010. The presence of symptoms suggestive of malaria infection in 982 women during antenatal visits (ANV), unscheduled visits and delivery were analysed. A multivariate logistic regression was used to determine the association between symptoms and a positive thick blood smear (TBS). Results During routine ANVs, headache was the only symptom associated with a higher risk of positive TBS (aOR = 1.9; p < 0.001). On the occasion of unscheduled visits, fever (aOR = 5.2; p < 0.001), headache (aOR = 2.1; p = 0.004) and shivering (aOR = 3.1; p < 0.001) were significantly associated with a malaria infection and almost 90% of infected women presented at least one of these symptoms. Two thirds of symptomatic malaria infections during unscheduled visits occurred in late pregnancy and long after the last intermittent preventive treatment dose (IPTp). Conclusion The majority of pregnant women were symptomless during routine visits when infected with malaria in an endemic stable area. The only suggestive sign of malaria (fever) was associated with malaria only on the occasion of unscheduled visits. The prevention of malaria in pregnancy could be improved by reassessing the design of IPTp, i.e. by determining an optimal number of doses and time of administration of anti-malarial drugs.